Trends in the prevalence of smoking in Portugal: a systematic review - Carreira, Helena (BioMed Central, 2012)
BACKGROUND: Understanding the dynamics of smoking at the population level is essential for the planning and evaluation of prevention and control measures. We aimed to describe trends in the prevalence of smoking in Portuguese adults by sex, age-group and birth cohort. METHODS: PubMed was searched from inception up to 2011. Linear regression was used to assess differences in prevalence estimates according to the type of population sampled, and to estimate time trends of smoking prevalence considering only the results of studies on nationally representative samples of the general population. RESULTS: Thirty eligible studies were identified. There were statistically significant differences in the prevalence estimates according to the types of population sampled in the original studies. Between 1987 and 2008, the prevalence of smoking increased significantly among women aged ≤ 70 years; the steepest increase was observed in those aged 31–50 and 51–70 years (from 4.6% and 0.1% in 1988, respectively, to 16.4% and 4.5% in 2008, respectively). The prevalence of smoking increased in all birth cohorts, except for those born before 1926. In the same period, among men, smoking decreased in all age-groups, with steepest declines in those aged ≤ 30 years (from 41.8% in 1988 to 28.8% in 2008) and those aged ≥ 71 years (from 15.1% in 1988 to 4.6% in 2008). The prevalence of smoking declined among men of all birth cohorts. CONCLUSIONS: This study provides robust evidence to place Portuguese women at stage II and men at the later stages of the tobacco epidemic.